In-treatment resolution or absence of electrocardiographic left ventricular hypertrophy is associated with decreased incidence of new-onset diabetes mellitus in hypertensive patients: the Losartan Intervention for Endpoint Reduction in Hypertension (LIFE) Study - Okin, Peter M; Devereux, Richard B; Harris, Katherine E; Jern, Sverker; Kjeldsen, Sverre E; Lindholm, Lars H; Dahlöf, Björn (Hypertension (Dallas, Tex. 1979), 2007)
Treatment of hypertensive patients with electrocardiographic left ventricular hypertrophy with losartan-based therapy is associated with lower incidence of diabetes mellitus and greater regression of hypertrophy than atenolol-based therapy. However, whether in-treatment resolution or continued absence of electrocardiographic hypertrophy is independently associated with decreased incidence of diabetes is unclear. Electrocardiographic hypertrophy was evaluated over time in 7998 hypertensive patients without diabetes at baseline in the Losartan Intervention For Endpoint reduction in hypertension (LIFE) study who were treated with losartan- or atenolol-based regimens and followed with serial electrocardiograms and blood pressure determinations. Electrocardiographic hypertrophy was defined using gender-adjusted Cornell voltage-duration product criteria >2440 mm.ms. During mean follow-up of 4.6+/-1.2 years, diabetes developed in 562 patients (7.0%). In a Cox model adjusting for treatment assignment, in-treatment resolution or continued absence of Cornell product hypertrophy was associated with a 38% lower risk of new diabetes (HR 0.62, 95% CI 0.50 to 0.78). After adjusting for the association of new diabetes with prior antihypertensive treatment, baseline glucose, and Framingham risk score, baseline and in-treatment systolic and diastolic pressure, HDL, uric acid, and body mass index, and the decreased incidence associated with losartan-based therapy, in-treatment continued absence, or resolution of Cornell product hypertrophy remained associated with a 26% lower risk of new diabetes (HR 0.74, 95% CI 0.58 to 0.93). Thus, compared with presence of hypertrophy by Cornell product criteria during antihypertensive treatment, resolution or continued absence of Cornell product hypertrophy is associated with a lower incidence of diabetes, even after adjusting for the impact of treatment with losartan and other risk factors for diabetes.